(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
In the first part of this essay, I consider why the discussion over the likelihood of imminent “peak oil” has faded from public view in the last few years. I suggest that, due to the decline in demand (due to the recession) and the development of “unconventional” natural gas and oil sources, the “cost” of fuels has passed from the obvious rise in price to that of another dimension: the rise of hidden, “external” costs—a recession triggered by too-high prices, pollution, climate change, and so on. I argue, moreover, that this externalized cost forever defies precise measurement. This is clear, for example, in the case of the “unconventional” production of gas in the “tar sands” region of Alberta. How can one measure the cost of drifting underground plumes of arsenic that may not show up for hundreds of years? All of this makes a precise calculation of “sustainability” just about impossible, while at the same time not absolving us—all of those living in the current fossil-fuel civilization—from attempting to calculate it. In the final part of the essay, I suggest that our subjectivity—as consumers, as free agents—is itself an after-effect of the agency of oil: we as subjects are interpellated by oil. Thus one response to the unknowability of externalities—tied to the impossibility of the “closed economy” of sustainability calculation—may be a different model of agency, in which calculation is replaced, or supplemented, by the act of gift-giving. Most important, perhaps, would be the giving of the gift of oil “addiction” not to any recipient (or agent), but to a necessarily repeated forgetting.